Indigenous Legal Traditions in Canada - John Borrows (Washington University Journal of Law & Policy, 2005)
Canada is a juridically pluralistic state, and draws on many sources of law to sustain order throughout the land. While civil and common law traditions are generally recognized nationwide, this is not always the case with indigenous legal traditions. Yet, indigenous legal traditions can have great force and impact in people’s lives despite their lack of prominence in broader circles. Indigenous legal traditions are a reality within Canada and should be more effectively recognized as such.
Keywords: Legal pluralism; Indigenous peoples – Canada; Multiculturalism – Canada